Cultural patterns of firewood use as a tool for conservation: A study of multiple perceptions in a semiarid region of Cordoba, Central Argentina - Martinez, Gustavo Javier (2015)
The paper analyzes local perceptions and practices related to the quality, extraction, and use of fuels firewood by the inhabitants of two protected areas. Our working model assumes the existence of patterns of preference, use and acquisition of firewood, depending on the social actors involved, and their perceptions. Our research developed through: the making of a reference collection and the applicationand of in-depth interviews and semi-structured surveys. We identified the most frequently used species and those with the greatest number of uses. The presence of patterns in the provisioning of energy source, and of firewood gathering and use, were identified in different actors. Through the application of a PCA analysis, and the study of native categories, patterning in the grouping of species was established, according to the local firewood classification. The latter relate to differences in the ease of ignition, in the durability and temperature of the flame and/or embers and the amount and type of smoke or ash produced. On the basis of ecological and perceptual information, a ranking of local priorities for the conservation of woody species is proposed. Finally, we discuss the relevance of sociocultural patterns of local perceptions of firewood use for conservation.